90 GASTRIC CANCER PRESENTING AS SUBACUTE COMBINED DEGENERATION OF THE SPINAL CORD. (1st March 2007) - Sircar, P.; Shetty, S.; Cheeran, B.; Akinyemi, E.; Niranjan, S.
Abstract : Introduction: In clinical practice, it is not uncommon to come across cases of subacute combined degeneration of the spinal cord in patients with pernicious anemia. The commonest cause of cobalamin deficiency is due to inadequate absorption associated with pernicious anemia. Vitamin B12 deficiency is also associated with gastrectomy and autoimmune metaplastic atrophic gastritis. Although chronic atrophic gastritis can lead to an increased risk of intestinal-type gastric cancer and gastric carcinoid tumor, presumably owing to prolonged achlorhydria resulting from parietal cell loss, it is very unusual for neurologic complications to be the primary manifestation in a patient with gastric cancer. We present a rare case of gastric adenocarcinoma presenting initially with neurologic complications of B12 deficiency. Case Report: A 48-year-old Caucasian gentleman came to the hospital complaining of gait disturbance for 3 to 4 weeks. Symptoms began with paresthesia in the lower extremities and gradually progressed to a point where he was unable to walk without support. He also complained of early satiety and dyspepsia for a few months. His past medical history and family history were essentially unremarkable. He drank moderate amounts of alcohol on a regular basis and also smoked one pack of cigarettes a day, both for 20 years. On examination, his abdomen was benign, but he had significant neurologic findings. His mental status and cranial nerves were intact. Motor strength was 4/5 in both lower extremities and tone was increased bilaterally. Sensory examination revealed hypoesthesia in both lower extremities. Vibration and position sense were absent bilaterally. Plantars were equivocal. Initial laboratory data were consistent with macrocytic anemia (peripheral smear showing hypersegmented neutrophils), with hemoglobin of 9 g/dL and MCV of 110 fl. The vitamin B12 level was on the lower side (210 pg/mL), with an increased B12 binding capacity (1, 637 pg/mL). Radiologic investigations of the spine were unremarkable, including MRI of the spine. The patient also underwent upper gastrointestinal endoscopy for evaluation of his dyspeptic symptoms, which revealed poorly differentiated gastric adenocarcinoma, well to moderately differentiated, in the background of acute and chronic gastritis. The specimen was negative for Helicobacter pylori . The patient was treated with vitamin B12, and his neurologic symptoms improved dramatically. He also underwent partial gastrectomy and did well thereafter. Discussion: The lesion in subacute combined degeneration of spinal cord is specific for cobalamin deficiency and is proposed to be due to a defect in myelin formation of unknown mechanism. Symptoms begin with paresthesia and ataxia associated with loss of vibration and position sense and can progress to severe weakness, spasticity, clonus, paraplegia, and even fecal and urinary incontinence. Early treatment with vitamin B12 can prevent many complications and permanent disability. Patients with atrophic gastritis may have an increased risk of developing gastric or colorectal adenocarcinoma, but the data are not entirely conclusive. There are no set recommendations to screen these patients at a greater frequency than the general population. Nevertheless, it is prudent to periodically monitor stools in these patients for the presence of blood. As the above case represents, gastric carcinoma rarely have an unusual presentation like our patient had, and a high index of suspicion for it can potentially be lifesaving in an otherwise near-fatal diagnosis.